Effect of Humulus lupulus L. (Hop) on Postmenopausal Sexual Dysfunction: A Randomized Clinical Trial - Zahra Vahedpoorfard; Samira Ferdosi; Habibollah Rahimi; Hossein Motedayyen (International Journal of Clinical Practice)
Objective. Female sexual dysfunction is a common distressing problem among women, which may result from reducing circulating endogenous estrogen. Humulus lupulus L. (hop) has antioxidant, anti-inflammatory, anticancer, and estrogenic properties. Therefore, this study aimed to assess the efficacy of hop on postmenopausal sexual dysfunction. Methods. In the current randomized clinical trial, study populations consisted of 63 postmenopausal women who were randomly categorized into two groups. In the hop group (N = 33), women received the vaginal gel containing Hop extract every day for seven days and then continued for two months, twice weekly. In the estradiol group (N = 30), women were treated with vaginal estradiol (0.625 mg) over two 28-day cycles (21 days of therapy and seven days rest). The sexual function was evaluated using the Female Sexual Function Index (FSFI) questionnaire before and after intervention. Results. No statistically significant differences in FSFI scores (sexual desire, sexual arousal, vaginal lubrication, satisfaction, orgasm, sexual pain, and total FSFI) (P > 0.05) were noticed after treatment between the hop and estradiol groups. Conclusion. Vaginal hop was as effective as estradiol in improving the sexual dysfunction among postmenopausal women with no adverse events. This trial is registered with IRCT20210405050859N1.